Surgeons’ experience in breast conserving surgery: does it influence surgical margin? - Shahrun Niza Abdullah Suhaimi,; Ussof Eskaandar MH,; Nani Harlina Md. Latar,; Razrim R,; Rohaizak Muhammad, (Faculty of Medicine, UKM Medical Centre, 2016)
A surgeon’s experience plays an important role in breast conserving surgery (BCS). The common conception is that, the more junior is the operating surgeon, the surgical margin will be wider or closer to the tumour edge. Thus the aim of this study is to look into the adequacy of surgical margin performed by different level of surgeons’ experience in patients whom underwent wide local excision (WLE) and hook-wire localization (HWL) in our surgical unit. The surgical experience of the operating surgeon and their surgical margins will be analyzed. This is a retrospective study from January 2000 to December 2012. Eighty-eight patients with early breast cancer underwent WLE and HWL by 3 different groups of surgeons (breast surgeons, junior surgeons and surgical registrars) were included. The surgical margins were analyzed for involved-margin, closed-margin or excessed-margin.The incidence of involved-margin, closed-margin and excessed-margin is the lowest among breast surgeons compared to other groups. However, the results were not statistically significant. The incidence of involved surgical margin is significantly higher within junior surgeons for HWL compared to the breast surgeons. The incidence of involved, closed or excessed surgical margin were lowest when performed by breast surgeon but not significantly different between the three groups. However, for HWL the breast surgeons significantly better compared to the other groups.